The Length-Weight Relationship and Condition Factor of Anabas testudineus in Tidal Flood Plains Mempawah Regency, West Kalimantan: Growth Pattern and Condition Facton Anabas testudineus in Tidal Flood Plains - Farid Mudlofar; Sarmila; Ridwan Salim; Rizal Akbar Hutagalung; Agus Setiawan; Susilawati; Suparmin (Journal of Aquaculture and Fish Health, 2026)
This study aims to analyze the length–weight relationship and condition factor of Anabas testudineus inhabiting the tidal floodplain ecosystem of Mempawah Regency, West Kalimantan, as a basis for assessing its physiological condition and ecological adaptation to environmental variation. Sampling was conducted at three stations representing different salinity gradients along the tidal floodplain system. A total of 300 individual fish (100 per station, consisting of 50 males and 50 females) were analyzed for total length and body weight. The results showed that the growth coefficient (b) varied among stations: Station 1 exhibited a negative allometric growth pattern (b < 3), Station 2 showed a positive allometric pattern (b > 3) in the combined population, and Station 3 displayed a positive allometric growth pattern (b > 3) in all groups. The condition factor (K) also varied among stations, with the highest average value recorded at Station 3 (1.191), indicating better physiological status and growth performance. Variations in growth and condition factor were influenced by differences in water quality, particularly salinity, dissolved oxygen, and natural food availability. Ecologically, these findings demonstrate the high adaptive capacity of A. testudineus to fluctuating tidal floodplain environments and highlight the importance of conserving low-salinity habitats to support sustainable biomass growth and management of freshwater fish populations.